ANALISIS KEMAMPUAN MEMBACA SISWA KELAS II SDS KARTIKA SILIWANGI - Hasya, Hasya Auliya Ummu Abiha; Gunawan , Dani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is an analysis of students' reading abilities conducted on second-grade students of SDS Kartika Siliwangi. The purpose of this study is to determine and describe the reading abilities of second-grade students of elementary school, factors that inhibit students' reading abilities, and efforts to overcome the reading difficulties of second-grade students of SDS Kartika Siliwangi. The method used in this study is a case study with a qualitative approach. Data collection techniques use observation, interviews, and documentation techniques. The results of this study indicate that the reading abilities of second-grade students of SDS Kartika Siliwangi, appear to be still low. Where students have not been able to identify double consonants, are still lacking in distinguishing letters that look the same, the ability to pronounce letter combinations in words is still low, still make mistakes in reading words. Factors that influence reading abilities, namely internal and external factors of students, the suggested solution to overcome low student reading abilities is to provide additional reading study hours, provide good library facilities.